Effect of concurrent action observation, peripheral nerve stimulation and motor imagery on dexterity in patients after stroke: a pilot study - Sarina Seitz; Corina Schuster-Amft; Jasmin Wandel; Leo H. Bonati; Katrin Parmar; Hans Ulrich Gerth; Frank Behrendt (Scientific Reports, 2024)
Abstract Research to improve and expand treatment options for motor impairment after stroke remains an important issue in rehabilitation as the reduced ability to move affected limbs is still a limiting factor in the selection of training content for stroke patients. The combination of action observation and peripheral nerve stimulation is a promising method for inducing increased excitability and plasticity in the primary motor cortex of healthy subjects. In addition, as reported in the literature, the use of action observation and motor imagery in conjunction has an advantage over the use of one or the other alone in terms of the activation of motor-related brain regions. The aim of the pilot study was thus to combine these findings into a multimodal approach and to evaluate the potential impact of the concurrent application of the three methods on dexterity in stroke patients. The paradigm developed accordingly was tested with 10 subacute patients, in whom hand dexterity, thumb-index pinch force and thumb tapping speed were measured for a baseline assessment and directly before and after the single intervention. During the 10-min session, patients were instructed to watch a repetitive thumb-index finger tapping movement displayed on a monitor and to imagine the sensations that would arise from physically performing the same motion. They were also repeatedly electrically stimulated at the wrist on the motorically more affected body side and asked to place their hand behind the monitor for the duration of the session to support integration of the displayed hand into their own body schema. The data provide a first indication of a possible immediate effect of a single application of this procedure on the dexterity in patients after stroke.